2021
DOI: 10.3390/pathogens10121587
|View full text |Cite
|
Sign up to set email alerts
|

HIV Pretreatment Drug Resistance Trends in Mexico City, 2017–2020

Abstract: In response to increasing pretreatment drug resistance (PDR), Mexico changed its national antiretroviral treatment (ART) policy, recommending and procuring second-generation integrase strand-transfer inhibitor (INSTI)-based regimens as preferred first-line options since 2019. We present a four-year observational study describing PDR trends across 2017–2020 at the largest HIV diagnosis and primary care center in Mexico City. A total of 6688 baseline protease-reverse transcriptase and 6709 integrase sequences we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
(23 reference statements)
3
4
0
Order By: Relevance
“…Results of the multivariable analysis indicated that individuals who had prior ARV drug exposure had 7.45 times greater odds of PDR compared to those without prior ARV drug exposure. Such findings are consistent with research from Mexico, African countries, and Northeast China [ 42 - 44 ]. There was an increasing trend of the proportion of CRF55_01B samples, rising from 2.3% in 2015 to 3.9% in 2018 and 4.1% in 2022 in China [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…Results of the multivariable analysis indicated that individuals who had prior ARV drug exposure had 7.45 times greater odds of PDR compared to those without prior ARV drug exposure. Such findings are consistent with research from Mexico, African countries, and Northeast China [ 42 - 44 ]. There was an increasing trend of the proportion of CRF55_01B samples, rising from 2.3% in 2015 to 3.9% in 2018 and 4.1% in 2022 in China [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…A few accessory mutations were identified in the integrase region, and no major level resistance was observed, consistent with other studies [ 17 , 18 , 19 ]. The L74M polymorphic mutation was commonly observed with a frequency of 0.5–20%, decreasing the effectiveness of the first- and second-generation INSTI drugs, as was previously reported in Brazil in a study of PDR on ART-naïve subjects [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
“…These findings align with studies conducted in Tianjin [ 32 ] and Cameroon [ 33 ]. It has been widely reported that EFV and NVP, as first-line drugs, are frequently associated with the development of resistance [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…After excluding 145 ART-naive individuals without sequence results, the final analysis included 1640 ART-naive individuals for PDR analysis and 569 ARTexperienced individuals for ADR analysis. Among the 1640 ART-naive individuals, the median age was 31 years (interquartile range (IQR) [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. The majority of participants were male (97.0%, 1590/1640), while a smaller proportion were female (3.5%, 50/1640).…”
Section: Demographic and Clinical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation